Experimental evaluation of the efficiency performance of the DMFC - Bayramoglu, Mahmut; Cigeroglu, Zeynep; Kazan, Emine Sena (Wiley, 2020)
This study represents the experimental assessment of the faradaic, fuel, and energetic efficiency of active direct methanol fuel cell (DMFC). The experimental system was equipped with several sensors, HPLC and UV spectroscopy to make on-line and off-line measurements of different components. A polarization study was conducted and an experimental plan was applied to collect the process data during 3-hour runs. Finally, stoichiometric and various efficiency calculations were performed based on the system and the process data. The results showed that the cell performance was better at higher operating temperatures (70.8 mW cm(-2) @75 degrees C). Faradaic efficiency and fuel efficiency were better at low temperatures and estimated as 55.8% and 59.6% at 55 degrees C, respectively. Energetic efficiency was better at higher temperatures due to the faster anode kinetics and was found as 12.3% at 75 degrees C. The efficiencies were strongly dependent on methanol concentration. Methanol crossover was increased with increasing methanol concentration; hence the efficiencies were decreased.
Keywords: direct methanol fuel cell; energetic efficiency; faradaic efficiency; fuel efficiency